Cost-effectiveness analysis of mRNA COVID-19 vaccine versus inactivated COVID-19 vaccine for mass vaccination in Jordan using a decision tree model - Qusai Abdulraheem AbuQamar; Aidalina Mahmud; Saba Madae'en; Norliza Ahmad; Lim Poh Ying; Azimatun Noor Aizuddin (Pharmacia)
Objectives: The purpose of this study was to present data regarding the most cost-effective vaccine for preventing COVID-19-related deaths. Methods: A mass immunization campaign using mRNA and inactivated COVID-19 vaccines was compared to no vaccination in a cost-effectiveness analysis. A hypothetical population of Jordanians aged 18 and over in 2021 was used to create a decision-tree model from the provider’s point of view. The main result was the prevention of COVID-19-related deaths. Government reports, observational primary costing studies employing the micro-costing approach, systematic reviews, and secondary data analysis at the national level were the sources of the model’s inputs. To take uncertainty into consideration, scenario analysis and one-way sensitivity analysis (OWSA) were performed. Results: mRNA vaccination, inactivated vaccination, and no vaccination strategies have corresponding total costs of 339,035,352.00 JOD, 643,192,339.62 JOD, and 1,110,731,145.64 JOD. It is anticipated that these strategies will result in 952, 6,505, and 29,324 deaths, respectively. The inactivated strategy’s incremental cost-effectiveness ratio (ICER) is 20,489.01 JOD per death averted, whereas the mRNA strategy’s is 27,199.20 JOD per death averted, making it the dominant strategy. The ICER was 54,773.45 JOD saved for every extra mortality prevented when comparing mRNA to the inactivated approach. When compared to the other techniques, the mRNA strategy maintained its dominance throughout alterations in the analysis, as demonstrated by the OWSA and the worst-case scenario analysis, suggesting robust outcomes. Conclusion: The mRNA vaccination strategy outperformed the inactivated vaccine and no-vaccination strategies in this study’s context in terms of preventing COVID-19 mortalities.